A constructivist learning event using computers at the Instituto Superior de Ciências de Educação (ISCED) - Angola - Cronje, Johannes Christoffel (University of Pretoria, 2013)
Dissertation (MEd (Computer Integrated Education))--University of Pretoria, 2007.